All-oral low-dose chemotherapy TEPIP is effective and well-tolerated in patients with peripheral T-cell lymphoma - Fante, Matthias A.; Harrer, Dennis C.; Zartner, Barbara; Lüke, Florian; Mayer, Stephanie; Menhart, Karin; Reichle, Albrecht; Herr, Wolfgang; Vogelhuber, Martin; Heudobler, Daniel (Frontiers in Oncology, 2023)
Purpose Peripheral T-cell lymphoma (PTCL) is a rare and heterogenous hematologic malignancy with poor prognosis especially in elderly and frail patients who are not eligible for intensive treatment. The resulting palliative setting necessitates tolerable but effective schedules for outpatient treatment. TEPIP is a locally developed, all-oral low-dose regimen comprising trofosfamide, etoposide, procarbazine, idarubicin, and prednisolone. Methods In this observational retrospective, single-center study, the safety and efficacy of TEPIP was evaluated in 12 patients (pts.) with PTCL treated at the University Medical Center Regensburg between 2010 and 2022. The endpoints were overall response rate (ORR) and overall survival (OS), and adverse events were individually reported according to the Common Terminology Criteria for Adverse Events (CTCAE) criteria. Results The enrolled cohort was characterized by advanced age (median 70 years), extensive disease (100% Ann Arbor ≥stage 3), and poor prognosis (75% high/high-intermediate international prognostic index). The most common subtype was angioimmunoblastic T-cell lymphoma (8/12), and 11/12 patients had relapsed or refractory disease at TEPIP onset with a median of 1.5 prior treatment regimens. After a median of 2.5 TEPIP cycles (total of 83 cycles), the ORR was 42% (complete remission 25%), and the OS reached a median of 185 days. Any grade of adverse event (AE) occurred in 8/12 patients, with four patients showing AE ≥CTCAE grade 3 (33%), and the AEs were mainly non-hematological. Conclusion TEPIP demonstrated competitive efficacy with a tolerable safety profile in a highly palliative cohort of patients with difficult-to-treat PTCL. The all-oral application, which makes outpatient treatment possible, is particularly noteworthy.